Diagnozowanie sprawności mówienia w perspektywie (nie tylko) egzaminu maturalnego - Nocoń, Jolanta (Polonistyka. Innowacje, 2015)
The article discusses the difficulties of diagnosing speaking skills in the situation of matriculation examination, resulting from the specific nature of spoken language varieties and texts implementation in these variants. Factors that should be taken into account when formulating criteria for assessing speech and conversation exams are: complex and holistic structure of spoken speech, transience of audible text, the spontaneity of live speech, the power of nonverbal codes, a significant stigma of a dialog, and the influence of situational context on the course of communicative interaction. The analysis of speaking skills assessment tools prepared for the oral examination in the year 2015 revealed that some of them had a significant impact on the criteria developed for this purpose.